Effectiveness of the health literacy promoting program among older adults with knee osteoarthritis in the rural Phayao Province - Pa-in, Porntip; Weiangkham , Dao (Thai Journal of Nursing, 2024)
The objective of this quasi-experimental study, two group pretest - posttest design, was to evaluate effectiveness of the health literacy promoting program among older adults with knee osteoarthritis in the rural Phayao province. A sample of 44 older adults with knee osteoarthritis living in a sub-district in Phayao province, was purposively selected. They were randomly assigned to the experimental group (n = 22) who received usual care and the health literacy promoting program and the comparison group (n = 22) who received usual care. Data were collected using questionnaire on demographic data and the European health literacy survey. Data were analyzed using descriptive statistics and t-test. The research findings revealed that after the implementation of the health literacy promoting program, the mean scores of health literacy in the experimental group were significantly higher than those in the comparison group and before the implementation of the health literacy promoting program at p < .001.